EFEK FRAKSI AKTIF BUAH MERAH (Pandanus conoideus Lamk.) TERHADAP PROLIFERASI SEL, EKSPRESI COX-2 DAN P53, SERTA AKTIVITAS FAGOSITOSIS MAKROFAG PADA KANKER PAYUDARA MODEL MENCIT C3 - , Lisna Hidayati, Prof. Dra. Sukarti Moeljopawiro, M. App. Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Breast cancer is the most common cancer among Indonesian woman. Recently, buah merah (Pandanus conoideus Lamk.) have been extensively used to treat cancer. The objective of this research were to analysize the effect of buah merah on cell proliferation, COX-2 and p53 mutant expression, and macrophages phagocytosis activity of C3H mice breast cancer model. Buah merah was obtained from Cycloups Sentani Papua. C3H donor and recipient were gained from Faculty of Medicine, University of Indonesia. Mammary tumor induction was done by injecting subcutaneously of 0.2 ml tumor cell suspension in the armpit area. Mice were randomly divided into 5 groups of 6, the first 2 groups used as controls. The active fraction was given orally 0,557mg/day for 21 days to the curative I